(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2012)
Tithonia diversifolia (Hemsl.) A. Gray is an Asteraceae shrub, popularly known as Mexican sunflower and cultivated for ornamental and therapeutic uses in different countries. In folk medicine, it is of value for treating diabetes, malaria and infectious diseases. These indications have been corroborated by various pharmacological assays. Given the lack of data on anatomical aspects of T. diversifolia, this work aimed to investigate the leaf and stem microscopic characters of this medicinal plant and potential vegetal drug. Samples of mature leaves and young stems were sectioned and stained. Histochemical tests and scanning electron microscopy were also performed. The leaf has anomocytic stomata on both sides, dorsiventral mesophyll and several collateral vascular bundles arranged as a ring in the midrib. The stem shows angular-tangential collenchyma, an evident endodermis and sclerenchymatic caps adjoining the phloem. The main characters for anatomical identification are the different types of trichome (non-glandular, capitate and non-capitate glandular), the midrib features and the localization of the secretory ducts near the vascular system.